Create success : - Doyle, Jon (McGaw-Hill, 2013)
Research shows the best chance a student has at success and persistence in college is to get involved and engaged with the school within 30 days of orientation through relationships, whether with an instructor, staff, or other students. Create Success provides students and instructors with the tools needed to foster these relationships. With agile social learning, instructors can immediately facilitate an active and engaged classroom environment and help students create connections with each other and the school community.